Virtual Reality For Android Based Parturition Simulation: Virtual Reality Untuk Simulasi Partus Berbasis Android - Muhammad Sayyi Syeh Putradifa; Yulian Findawati (Universitas Muhammadiyah Sidoarjo, 2021)
The purpose of making this application is to facilitate the practice of learning the parturition process (childbirth) for midwifery academics. The method used is in the form of virtual reality applications, namely technology that has the potential to produce real conditions in the form of 3D objects and virtual environments to the user, in this case the simulation of parturition (childbirth). The results of making this application are used to make it easier for academics in the learning process, because for now what we know for the learning process and practice is still with aids in the form of visual aids that can only be found in hospitals or medical and midwifery schools. The benefits of using this application are to make it easier for midwifery academics in the learning process for parturition(childbirth).